Near-real-time monitoring of global CO(2) emissions reveals the effects of the COVID-19 pandemic - Liu, Zhu (Nat Commun, 2020)
The COVID-19 pandemic is impacting human activities, and in turn energy use and carbon dioxide (CO(2)) emissions. Here we present daily estimates of country-level CO(2) emissions for different sectors based on near-real-time activity data. The key result is an abrupt 8.8% decrease in global CO(2) emissions (−1551 Mt CO(2)) in the first half of 2020 compared to the same period in 2019. The magnitude of this decrease is larger than during previous economic downturns or World War II. The timing of emissions decreases corresponds to lockdown measures in each country. By July 1st, the pandemic’s effects on global emissions diminished as lockdown restrictions relaxed and some economic activities restarted, especially in China and several European countries, but substantial differences persist between countries, with continuing emission declines in the U.S. where coronavirus cases are still increasing substantially.